Mobilization of hematopoietic stem cells with the novel CXCR4 antagonist POL6326 (balixafortide) in healthy volunteers—results of a dose escalation trial. Issue 1 (December 2017) - Karpova, Darja; Bräuninger, Susanne; Wiercinska, Eliza; Krämer, Ariane; Stock, Belinda; Graff, Jochen; Martin, Hans; Wach, Achim; Escot, Christophe; Douglas, Garry; Romagnoli, Barbara; Chevalier, Eric; et al.
Abstract Background Certain disadvantages of the standard hematopoietic stem and progenitor cell (HSPC) mobilizing agent G-CSF fuel the quest for alternatives. We herein report results of a Phase I dose escalation trial comparing mobilization with a peptidic CXCR4 antagonist POL6326 (balixafortide) vs. G-CSF. Methods Healthy male volunteer donors with a documented average mobilization response to G-CSF received, following ≥6 weeks wash-out, a 1–2 h infusion of 500–2500 µg/kg of balixafortide. Safety, tolerability, pharmacokinetics and pharmacodynamics were assessed. Results Balixafortide was well tolerated and rated favorably over G-CSF by subjects. At all doses tested balixafortide mobilized HSPC. In the dose range between 1500 and 2500 µg/kg mobilization was similar, reaching 38.2 ± 2.8 CD34 + cells/µL (mean ± SEM). Balixafortide caused mixed leukocytosis in the mid-20 K/µL range. B-lymphocytosis was more pronounced, whereas neutrophilia and monocytosis were markedly less accentuated with balixafortide compared to G-CSF. At the 24 h time point, leukocytes had largely normalized. Conclusions Balixafortide is safe, well tolerated, and induces efficient mobilization of HSPCs in healthy male volunteers. Based on experience with current apheresis technology, the observed mobilization at doses ≥1500 µg/kg of balixafortide is predicted to yield in a single apheresis a standard dose of 4× 10E6 CD34+ cells/kg from most individuals donating for an approximately weight-matched recipient. Exploration of alternative dosing regimens may provide even higher mobilization responses. Trial Registration European Medicines Agency (EudraCT-Nr. 2011-003316-23) andclinicaltrials.gov (NCT01841476)